Estimating productivity of water at different spatial scales using simulation modeling - Droogers, Peter; Kite, G.W. (International Water Management Institute, 2001)
A clear understanding of the current water balance is required to explore options for water saving measures. However, measurement of all the terms in the water balance is infeasible in terms of spatial and temporal scale, but hydrological simulation models can fill the gap between measured and required data. For a basin in Western Turkey, simulation modeling at three different scales, field, irrigation scheme and basin scale, was performed to obtain all terms of the water balance. These water balance numbers were used to calculate the Productivity of Water at the three spatial levels distinguished to assess the performance of the systems.